Peningkatan Kadar Insulin Serum Tikus Wistar Jantan Model Hiperglikemia Akibat Pemberian Infusa Daun Sambiloto, Daun Salam, Kayu Manis, Dan Rimpang Temulawak - Andi Nadya Sahnaz (Jurnal Kedokteran Komunitas (Journal of Community Medicine), 2018)
Introduction: Diabetes mellitus is a metabolic disorder characterized by hyperglycemia due to insulin secretion and sensitivity defects. Sambiloto leaves, bay leaves, cinnamon, and ginger rhizomes have the potential for antihyperglycemia and antioxidants. However, research on the herbal combination to serum levels of insulin has not been done. The purpose of this study was to prove the effects of combined sambiloto leaves, bay leaves, cinnamon, and ginger rhizomes infusion on serum insulin levels of hyperglycemic rats.Methods: Laboratory experimental in vivo with the control group post test only design using male Wistar rats aged 2-3 months. Rats were divided into five groups, KN (n = 5), KP (n = 5), KP 1 (SSKT dose 125 mg/kgBB, n=5), KP 2 (SSKT dose 250 mg/kgBB, n=5), KP 3 (SSKT dose 500 mg/kgBB, n=5). Serum insulin level was measured using the Rat Insulin ELISA kit. Data were analyzed using One Way ANOVA and Post Hoc LSD test. The results are said to be significant if (p <0.05).Result: Induction of STZ and HFD on KP did not show a significant difference compared to KN. There was no significant difference between KP 1 group with KP, but KP 2 and KP 3 were significantly higher (p<0.05) respectively 16% and 14% compared to KP. While on KP 2 did not show a significant difference on KP 3.Conclusion: The combination of sambiloto leaves, bay leaves, cinnamons and ginger rhizomes infusion dosages of 250mg/kgBB and 500mg/kgBB can increase serum insulin levels of hyperglycemia rats.